Efficacy of Sirolimus in a 17-Month Old Patient with Primary Intestinal Lymphangiectasia - Alsuqayhi, Saleh; Swaidi, Azhar; Alyousef, Ammar; Alhebbi, Homoud; Alamrani, Mohammed (International Journal of Innovative Research in Medical Science, 2024)
Primary intestinal lymphangiectasia (PIL) is an uncommon condition characterized by the dilation of lymphatic vessels that supply the small intestinal wall, leading to the leakage of lymph into the small-bowel cavity. This causes a protein-losing enteropathy, resulting in decreased lymphocytes, low albumin levels, and reduced gamma globulin levels 1. Typically diagnosed before the age of three, PIL rarely occurs in adults. Here, we describe the case of a severely affected one-year-old Saudi girl with PIL, showing poor response to standard treatments. Initially diagnosed at four months of age through lymph scintigraphy, endoscopy, and histopathology. she experiences recurring swelling in her upper and lower limbs, ascites, genital swelling, and diarrhea. She requires frequent albumin transfusions every two weeks to manage her symptoms, despite most standard therapies proving ineffective in maintaining remission. Interventions like monogen formula alone have been insufficient. However, the introduction of sirolimus has significantly reduced her hospital admissions and need for albumin transfusions to once every four to six weeks. She is presently undergoing sirolimus therapy along with fat-soluble vitamins (ADEK) and a low-fat diet supplemented with medium-chain triglycerides.